Analisis pengaruh makroekonomi terhadap dana pihak ketiga (DPK) dengan equivalent rate (ER) sebagai variabel intervening - Salma Firdayanti Salma; Yusvita Nena Arinta Nena (IAIN Langsa, 2021)
This study aims to determine the Effect of Macroeconomics on Third-Party Funding (TPF) with the Equivalent Rate (ER) as the Intervening Variable (Case Study of Islamic Commercial Banks Period 2016-2020). This type of research is quantitative research which utilizes secondary data in the form of time-series data. Purposive sampling was used as the sampling method. The data that has been obtained later processed using the E-views version 9 application tool. Based on the results, it is shown that the Inflation, BI Rate, and Equivalent Ratevariables partially have a negative effect on TPF, while the Exchange Rate has a positive effect on TPF. Moreover, the variables of Inflation, Exchange Rate, and BI Rate have a positive and significant effect on the Equivalent Rate (ER). It is also found thatThe Equivalent Rate variable cannot mediate the effect of Inflation, Exchange Rate, and BI Rate on TPF.